Late Mesozoic marine Antarctic fishes: future perspectives based on the newly collections recovered at Ameghino and López de Bertodano formations - Gouiric Cavalli, Soledad (2017)
Fil: Gouiric Cavalli, Soledad. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Museo de La Plata. División Paleontología Vertebrados. Buenos Aires, Argentina.